An Empirical Study on Occupational Stress and Job Satisfaction of Employees in Private Banks in Northern Region of Sri Lanka - Aravinthon, A.S.; Velnampy, T. (JUICE- 2012 University of Jaffna, 2012)
Stress may prove an asset as long as it is tolerable and helps in creating healthy competition. Organizational excellence and individual success are achieved via well managed stress. Nowadays all organizations have recognized the fact that an organization can gain competitive advantage in market only if it has employees who posses positive work related attitudes. Literature of occupational stress highlights that occupational stress has the influence on the organizational activities and especially job satisfaction of employees. The negative characteristics of jobs, not only create stressful, emotional mental and physical state within the work setting, but also create stressful conditions in the nonworking life. These negative or stressful job characteristics could result in both negative work outcomes. The study was made to identify and measure the factors which determine the occupational stress and job satisfaction with the sample of 291 respondents in 04 private banks (16 Branches) in Northern Province of Sri Lanka. The relationship between occupational stress and job satisfaction and impact of occupational stress on job satisfaction were also identified, using appropriate tools. Majority of the respondents are in the lower level component of occupational stress and job satisfaction respectively, constituting 86.7% and 8.95% whereas only 5.3% and 0.4% of respondents are at the high level component of occupational stress and job satisfaction respectively. Descriptive statistics revealed that the physical environments of occupational stress, basic and sociological needs of job satisfaction are highly rated with the mean and standard deviation. Study found a relationship between occupational stress and job satisfaction (0.369, p>0.01). All six components such as physical environment, organizational factors, job design, management practices, career development and social stressors are correlated with job satisfaction. According to 𝑅2 value (0.121), occupational stress is contributed to determine the job satisfaction by 12.1%. Significant difference between personal characteristics on occupational stress and job satisfaction was also identified in this study. There were no significant difference between gender group, marital status, monthly income, position and family size on the variable of occupational stress & job satisfaction.
Keywords: Job attitudes; Job satisfaction; Occupational stress